Thermal conductivity of ultra-wide bandgap thin layers – High Al-content AlGaN and β-Ga2O3 - Tran, Dat Q.; Blumenschein, Nicholas; Mock, Alyssa; Sukkaew, Pitsiri; Zhang, Hengfang; Muth, John F.; Paskova, Tania; Paskov, Plamen P.; Darakchieva, Vanya (Physica B: Condensed Matter, 2020)
Transient thermoreflectance (TTR) technique is employed to study the thermal conductivity of β-Ga2O3 and high Al-content AlxGa1-xN semiconductors, which are very promising materials for high-power device applications. The experimental data are analyzed with the Callaway's model taking into account all relevant phonon scattering processes. Our results show that out-of-plane thermal conductivity of high Al-content AlxGa1-xN and (−201) β-Ga2O3 is of the same order of magnitude and approximately one order lower than that of GaN or AlN. The low thermal conductivity is attributed to the dominant phonon-alloy scattering in AlxGa1-xN and to the strong Umklapp phonon-phonon scattering in β-Ga2O3. It is also found that the phonon-boundary scattering is essential in thin β-Ga2O3 and AlxGa1-xN layers even at high temperatures and the thermal conductivity strongly deviates from the common 1/T temperature dependence.
Publisher Copyright: © 2019 Elsevier B.V.
Keywords: AlGaN; GaO; Thermal conductivity